An Analysis of the Risk‐Return Characteristics of Serially Correlated Managed Futures. Issue 10 (4th February 2016) - Elaut, Gert; Erdős, Péter; Sjödin, John
Abstract : We investigate the implications of low but persistent serial correlation in Managed Futures' returns for portfolio management. Using a measure based on the unweighted sum of autocorrelations, we find that more positively autocorrelated Managed Futures exhibit distinctly different risk‐return profiles and outperform, on a risk‐adjusted basis, Managed Futures that exhibit lower degrees of serial correlation. The observed premium is unlikely to be explained by a concentration in certain strategies, fund size and age, attrition or delisting bias, and does not seem to hamper Managed Futures' portfolio benefits as a tail‐risk hedge. © 2016 Wiley Periodicals, Inc. Jrl Fut Mark 36:992–1013, 2016